Study on the hydration of Portland cement paste replaced with blast furnace slag, fly ash, and metakaolin: effect on the usage of two superplasticizer additives - Gómez-Zamorano, L. Y.; García-GuillénG.; Acevedo-Dávila, J. L. (Revista ALCONPAT, 2015)
This research was focused on assessing the impact that different replacement materials and two superplasticizers on the development of the mechanical properties, phases formation and heat evolution of portland cement pastes, with replacement levels up to 60%. For this purpose, fly ash, ground granulated blast furnace slag, metakaolin and silica fume were used. The mixtures were manufactured with a water/solid of 0.4, 0.3% of superplasticizer and cured up to 60 days. Results showed that with the use of replacement materials, the calcium hydroxide content was reduced, due to the pozzolanic reaction, and the compressive strength was increased. Keywords: Reactivity, supplementary cementitious materials.